Indirect Electrochemical Analysis of Crocin in Phytochemical Sample - Riyaz Ahmad Dar; Pradeep Kumar Brahaman; Sweety Tiwari; Krishna Sadashiv Pitre (E-Journal of Chemistry)
A new electroanalytical method has been developed for the quantitative determination of crocin in a sample of stigmas of saffron (Crocus sativus L.). Crocin is polarographically inactive. However, cysteine in 0.02 M NaCl, pH=5.2±0.01 produces a well defined wave/peak with E1/2/Ep= –0.47/–0.45 V vs. Ag/AgCl. On recording polarograms of a set of solution containing a fixed concentration of cysteine and varying concentrations of crocin under aforesaid experimental conditions a gradual decrease in peak height/diffusion current and a negative shift in peak potential was observed. Thus, indicating cysteine-crocin interaction. Amperometric titration indicated crocin to cysteine ratio of 1:2. The above amperometric titration procedure has been used to determine the concentration of crocin in a sample of saffron. Crystallization process was carried out for the extraction of crocin from dried powder of saffron stigmas. The crystallized crocin was identified by UV-Visible spectrophotometry(at 255 nm and 442 nm) and the quantitative analysis by the developed amperometric method. The concentration of crocin in saffron was found to be 2.13% and purity of isolated crocin 96.81%. The percent recovery varied from 98.56–100.31% and RSD (n=5) of 2.17%.The validation of the proposed procedure for the quantitative assay of crocin was examined via an evaluation of the repeatability, recovery, selectivity and relative standard deviation.